Pengaruh Kepuasan Kerja Dengan Kinerja Perawat Instalasi Rawat Inap RSUD Sinjai - Munira; Batara, Andi Surahman; Haeruddin (Pusat Kajian dan Pengelolaan Jurnal FKM UMI, 2025)
One of the vital human resources (HR) in a hospital is related to its health workers, especially nurses. This is because the total need for nurses is the most significant proportion in a hospital compared to other health workers. Half of the number of nurses in Indonesia experience stress due to work. The impact is the behavior of nurses who are often late due to workload stress, and many of them take leave due to health problems. This study aims to determine the effect of job satisfaction on nurse performance in the Inpatient Installation of Sinjai Hospital. The type of research used in this study is quantitative research, which requires an approach to research proposals, processes, hypotheses, observations, data analysis, and conclusions, which are obtained through various measurement factors and the certainty of numerical data. The sampling technique is the same number of samples as the population. The population of this study was all nurses in the Inpatient Installation of Sinjai Hospital, totaling 108 nurses. Data was obtained through a questionnaire. The analysis method applied was univariate and bivariate analysis through the chi-square test. This study's results indicate an influence of Incentives on nurse performance (p-value = 0.036 > 0.05%). There is no influence of promotion on nurse performance (p-value = 0.179 <0.05%). Supervision influences nurse performance (p-value = 0.000 > 0.05%). The work influences nurse performance (p-value = 0.001 > 0.05%). There is an influence of co-workers on nurse performance (p-value = 0.004 > 0.05%). From the results obtained, it is expected that the hospital will pay attention to and ensure a supportive work environment for nurses, which is crucial for their well-being and performance.